1987
DOI: 10.1016/0742-8413(87)90148-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cadmium and zinc on steroid metabolism and steroid level in the sea star Asterias rubens L.

Abstract: Steroid metabolism was studied in gonads and pyloric caeca of male and female sea stars which had been exposed to cadmium or zinc for 3 weeks. Steroid metabolism had increased in animals exposed to heavy metals. Significant increase of the enzyme activity was observed for 17 alpha-hydroxylase in the pyloric caeca of female animals exposed to zinc (pregnenolone----17 alpha-hydroxypregnenolone) or cadmium (progesterone----17 alpha-hydroxyprogesterone), for 17 beta-hydroxysteroiddehydrogenase in the gonads of fem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

1989
1989
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…More clearly supporting the notion of sequential evolution of steroidogenesis steps are the observations of the conversion of cholesterol into PRG, and PRG to androgens, in the sea star Asterias rubens (Lafont and Mathieu, 2007; Schoenmakers and Voogt, 1981; Schoenmarkers and Voogt, 1980; Voogt et al, 1987). However, no estrogen aromatization has been found to occur in A. rubens or in A. vulgaris , consistent with the idea that CYP19 aromatase evolved after CYP11 and CYP17 (Hines et al, 1992; Schoenmakers and Voogt, 1981).…”
Section: Discussionmentioning
confidence: 59%
“…More clearly supporting the notion of sequential evolution of steroidogenesis steps are the observations of the conversion of cholesterol into PRG, and PRG to androgens, in the sea star Asterias rubens (Lafont and Mathieu, 2007; Schoenmakers and Voogt, 1981; Schoenmarkers and Voogt, 1980; Voogt et al, 1987). However, no estrogen aromatization has been found to occur in A. rubens or in A. vulgaris , consistent with the idea that CYP19 aromatase evolved after CYP11 and CYP17 (Hines et al, 1992; Schoenmakers and Voogt, 1981).…”
Section: Discussionmentioning
confidence: 59%
“…Aquatic pollutants, including pesticides, plasticizers, and detergent metabolites can disrupt endocrine function in vertebrates and invertebrates (Voogt et al 1987, Monod et al 1993, Purdom et al 1994, Harries et al 1997, Shurin & Dodson 1997, Zou & Fingerman 1999, Billinghurst et al 2000. Endocrine disruption occurs through several mechanisms, including mimicking or blocking action of endogenous hormones, particularly estrogens (Katzenellenbogen 1995, McLachlan 2001.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research also reported altered steroid metabolism and levels, evidence of disruptive action on the mono-oxygenase (MO) system, as well as reduced ovary growth and offspring quality in pyloric caeca and/or gonads of the asteroid A. rubens following exposures to different suspected EDCs, such as cadmium, PCBs and zinc (den Besten et al 1989(den Besten et al , 1991aVoogt et al 1987). Sea urchin gametes and larvae turned out to be very useful tools to assess deleterious effects of many chemicals, including EDCs, because of their high sensitivity and relatively easy handling (Angelini et al 2005;Schröder et al 2005).…”
Section: Introductionmentioning
confidence: 93%
“…In contrast, no clear evidences of sexual dimorphism were detected in the echinoid Lytechinus variegatus and Paracentrotus lividus, where both males and females had higher levels of testosterone than estradiol in gonads ). Finally, key steps of vertebrate-like steroidogenesis leading to the synthesis of androgens have also been described in Asterias rubens (Schoenmakers 1979;Voogt et al 1987;Hines et al 1992b) and in L. variegatus (Wasson et al 1998;.…”
Section: Introductionmentioning
confidence: 95%